Method for producing a composite glass pane
By using a layered frame made of optically transparent curable adhesives and thermoplastic materials in composite glass plates to integrate electro-optical functional films, the problems of electro-optical functional film integration problems and optical defects in composite glass plates are solved, and efficient and reliable Mass production of composite glass plates.
Patent Information
- Application Number
- CN202380051362.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-01
- Filing Date
- 2023-07-19
- Publication Date
- 2025-02-18
AI Technical Summary
The prior art is difficult to effectively integrate the object-main film as an electro-optical functional element in the industrial mass production of composite glass plates, and due to the unevenness of mechanical loads, local optical defects are easily caused.
By forming an adhesive film layer made of optically transparent curable adhesive between two single glass plates of the composite glass plate and embedded with an electro-optical functional film therein, a layered frame made of thermoplastic material and a thermoplastic film are stabilized by forming an adhesive film layer made of optically transparent curable adhesive between two single glass plates of the composite glass plate and embedded with an electro-optical functional film. Formation pressing ensures that the adhesive has sufficient fluidity during lamination to absorb uneven pressure loads.
It realizes the production of composite glass plates with high optical quality in industrial mass production, avoids uneven contact pressure on the electro-optical functional film, reduces the risk of local optical defects, and ensures the efficiency and reliability of composite glass plates.
Smart Images

Figure CN119486878A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of glass plate production, and relates to a method for producing a composite glass plate, a composite glass plate produced by the method according to the present invention, and a use thereof. Background Art
[0002] Composite glass panels usually consist of two single glass panels, usually made of glass, which are firmly joined to each other by at least one thermoplastic interlayer. Modern composite glass panels, in particular windshield panels of motor vehicles, can have complex curvatures in the horizontal and / or vertical direction in order to meet the aerodynamic requirements and design specifications of automobile manufacturers. They also increasingly include electrically controllable functional elements, which display information for the driver and / or front passenger, serve as lighting devices and / or can change the optical transparency of the glass panel, for example in the form of a sun visor. In particular, the optical transparency of the glass panel can be switched over a large area, for example in the top glass panel, the rear side glass panel or the partition glass panel. Electrically controllable functional elements in the form of electro-optical functional films are advantageously introduced into the composite glass panel. In particular, electro-optical functional films with liquid crystal-based functional layers (which are based on the so-called "guest-host" effect) mark the interesting possibility of realizing electro-optical switching functions in composite glass panels in a simple, space-saving, cost-effective and reliable manner in applications. Here and below, for simplicity, the electro-optical functional film having a liquid crystal-based functional layer based on the "guest-host" effect is referred to as a "guest-host film".
[0003] The guest-host film usually comprises a nematic liquid crystal (host) which is provided with an additive (guest), wherein, for example, dichroic dye molecules which absorb light anisotropically are used as additives. Since the molecules of the additive have an elongated form, their orientation can be controlled by the orientation of the liquid crystal molecules (i.e., the host), which is achieved in practice by applying an electric field to the liquid crystal. In this way, for example, the optical transparency of the guest-host film can be controlled very precisely by an external electric field. For example, a windshield can thus be provided very advantageously with an electrically switchable transparency in the manner of a sun visor.
[0004] Until now, it has not been possible to introduce guest-host films into composite glass panes by means of conventional lamination methods used in industry. The reason for this is that guest-host films cannot yet be integrated into conventional production processes for producing composite glass panes. In fact, this represents a great challenge for the simple and cost-effective industrial mass production of composite glass panes with guest-host films. As practice has shown, due to their physical properties, which are like those of liquids, guest-host films react very sensitively to mechanical loads caused by uneven contact pressure. During the lamination of the composite glass panes and in the laminated composite glass panes, even the smallest local deviations in the contact pressure lead already to local optical defects in the guest-host film, which can render the composite glass pane unusable.
[0005] However, in the mass production of curved composite glass panes, it is inevitable that the individual glass panes of the composite glass pane have shapes that do not match exactly. On the contrary, slight deviations of the shape always occur within the usual dimensional tolerances, which lead to locally higher pressure loads during the lamination process. In the case of conventional composite glass panes, this is of no consequence, since these locally higher pressure loads do not impair the optical quality of the composite glass pane. On the contrary, these locally higher pressure loads are sufficient to produce undesirable local optical defects (e.g. local discoloration or discoloration or turbidity) in the guest-host film. Moreover, in the production of composite glass panes, local shape deviations or locally higher pressure loads can be completely desirable.
[0006] To date, no method is known from the prior art for laminating composite glass panes which allows the industrial mass production of composite glass panes having a guest-host film integrated into the composite glass pane as an electro-optical functional element of usable optical quality.
[0007] WO 2021 / 069354 A1 discloses a composite glass pane with an integrated functional film, wherein an adhesive thin layer (not combined with a thermoplastic film) is located on one side of the functional film and a thermoplastic film (not combined with an adhesive thin layer) is located on the other side of the functional film.
[0008] WO 2021 / 249801 A1 discloses a method for producing a composite glass pane with an integrated functional film, wherein only thermoplastic films are used in order to avoid mechanical pressure loading of the functional film. Summary of the invention
[0009] In contrast, the object of the present invention is to provide an improved method for producing composite glass panes with an integrated guest-host film, by which composite glass panes with high optical quality can be produced in industrial mass production. In particular, the method should be usable in existing production plants, so that composite glass panes with an integrated guest-host film should be able to be produced in large quantities in a simple, cost-effective and reliable manner.
[0010] These and further objects are achieved according to the proposal of the invention by a method for producing a composite glass pane with an electro-optical functional film according to the independent claim. Advantageous embodiments of the invention result from the dependent claims.
[0011] According to the invention, a method for producing a composite glass pane, in particular a composite vitreous glass pane, with an integrated electro-optical functional film is shown. The electro-optical functional film is integrated into the composite glass pane, ie it is located between the two individual glass panes of the composite glass pane.
[0012] The method for producing a composite glass pane comprises the following steps, which are performed, for example but not necessarily, in the order indicated by the alphabetical designations:
[0013] Step (a)
[0014] A first stacking sequence is formed, which includes, in the following order:
[0015] - a first adhesive film made of an optically clear curable adhesive,
[0016] -Electro-optical functional film,
[0017] - A second adhesive film made of an optically clear curable adhesive.
[0018] Step (b)
[0019] A layered frame made of thermoplastic material is formed around the first stacking sequence.
[0020] Step (c)
[0021] A second stacking sequence is formed, which includes, in the following order:
[0022] - a first glass sheet,
[0023] - at least one first thermoplastic film,
[0024] - a previously produced first stacking sequence with a layered framework,
[0025] - at least one second thermoplastic film,
[0026] - Second glass plate.
[0027] Step (d)
[0028] The second stacking sequence is laminated under the action of heat and pressure.
[0029] Step (e)
[0030] The optically clear adhesive is cured.
[0031] During the lamination of the second stacking sequence in step (d), the thermoplastic film softens due to the increased temperature, i.e. a decrease in the viscosity or an increase in the fluidity of the thermoplastic occurs. In this way, the thermoplastic can melt and, after cooling (i.e. solidification), form a firm bond with the adjacent components. However, the composite glass panes are not yet firmly bonded. A firm bond of the composite glass panes does not exist until the curable adhesive has cured.
[0032] In the sense of the present invention, the term “laminating” describes the application of heat and pressure to the second stacking sequence and the cooling of the second stacking sequence until the thermoplastic plastic layer solidifies.
[0033] The adhesive film made of the optically transparent curable adhesive is melted due to the temperature increase during the lamination process of step (d), wherein the curable adhesive is designed so that the viscosity of the adhesive decreases or the fluidity increases by the heat during the lamination process of step (d).
[0034] The optically transparent curable adhesive is preferably designed such that the (absolute) viscosity of the curable adhesive (of the first and second adhesive films) decreases more strongly than the (absolute) viscosity of the thermoplastic (of the first thermoplastic film, the second thermoplastic film and the layered frame). In other words, due to the temperature increase during the lamination process, the curable adhesive is more fluid than the thermoplastic.
[0035] Therefore, during the lamination process of step (d), as the temperature increases, a decrease in the viscosity of the thermoplastic and a decrease in the viscosity of the optically transparent curable adhesive occur, wherein it is particularly preferred that, at least from the (lowest) temperature depending on the materials used, the viscosity of the optically transparent curable adhesive is lower than the viscosity of the thermoplastic, i.e. the fluidity of the optically transparent curable adhesive is greater than the fluidity of the thermoplastic. During the temperature increase during the lamination process of step (d), the viscosity of the optically transparent curable adhesive may always be lower than the viscosity of the thermoplastic. However, it is also possible that during the temperature increase during the lamination process of step (d), the viscosity of the optically transparent curable adhesive is lower than the viscosity of the thermoplastic only from the (lowest) temperature depending on the materials used. If the optically transparent curable adhesive is heat-curable, once crosslinking begins, the viscosity increases again with further increase in temperature. In any case, in this case there is also a temperature range in which the viscosity of the optically transparent curable adhesive is lower than the viscosity of the thermoplastic.
[0036] In the sense of the present specification, the term "viscosity" always refers to absolute viscosity, so the reduction of viscosity involves a reduction in absolute viscosity. According to conventional understanding, viscosity describes the viscosity or fluidity of a substance, wherein the lower the viscosity, the greater the fluidity, and vice versa. In the sense of the present invention, the dynamic viscosity, which is usually measured in millipascal seconds (mPas), can be regarded as viscosity. The viscosity can be measured by a measuring method familiar to those skilled in the art per se, for example by a rotational rheometer, wherein the only important thing is to use the same measuring method when measuring the viscosity of the thermoplastic and the optically transparent curable adhesive. Therefore, the comparison of the viscosity of the thermoplastic and the optically transparent curable adhesive is based on the same temperature (and the same pressure) and the same measuring method for measuring viscosity, for example preferably by a rotational rheometer, whose structure and mode of operation are familiar to those skilled in the art, so there is no need to discuss it here.
[0037] In the method according to the invention, it is particularly preferred that, at least starting from the (lowest) temperature depending on the materials used, the viscosity of the optically transparent curable adhesive is lower than the viscosity of the thermoplastic, i.e. the flowability of the optically transparent curable adhesive is greater than the flowability of the thermoplastic. The viscosities can be determined individually, i.e. outside the second stacking sequence.
[0038] During the lamination process of step (d), pressure is applied to the second stacking sequence only when the viscosity of the optically transparent curable adhesive of the two adhesive films is so strongly reduced due to the temperature increase that possible local inhomogeneities in the pressure load can be absorbed by the optically transparent curable adhesive, thereby uniformly applying pressure to the electro-optical functional film. It should be understood that during the application of pressure to the second stacking sequence in step (d), the curable adhesive has not yet been cured.
[0039] "Applying pressure" in the sense of the present invention is generally understood to mean a pressure increased relative to the ambient pressure, which is applied to the second stacking sequence. It should be understood that applying a very low pressure that is ineffective for lamination will not produce any local optical effect in the electro-optical functional film. The term "applying pressure" can also be reasonably understood to mean applying a pressure that is effective for lamination to the second stacking sequence. In any case, during the application of pressure to the second stacking sequence, the viscosity of the optically transparent curable adhesive must be so low that local inhomogeneities in the pressure can be absorbed by the curable adhesive.
[0040] Advantageously, pressure is applied to the second stacking sequence during lamination in step (d), in particular with a pressure effective for lamination, in particular with the maximum pressure used during lamination, only when the viscosity of the optically transparent curable adhesive reduced by heating during lamination in step (d) is lower than the viscosity of the thermoplastic reduced by heating during lamination in step (d).
[0041] The present invention thus advantageously shows a new method of how to minimize or even completely avoid the uneven contact pressure on the electro-optical functional film caused in particular by local shape deviations of the two glass plates during the lamination process. To this end, the electro-optical functional film is not laminated separately between two thermoplastic intermediate films, which are usually at least unable to fully absorb the local load peaks due to insufficient viscosity reduction for this. Instead, the electro-optical functional film is embedded between two layers made of the optically transparent curable adhesive, which undergo such a viscosity reduction (increased fluidity) during the lamination process due to the increase in temperature that they can absorb the uneven load pressure on both sides of the electro-optical functional film. The local load peak when the electro-optical functional film is pressed between the two glass plates during the lamination process can thus be effectively avoided or at least so strongly reduced that optical defects are prevented from occurring in the electro-optical functional film. Therefore, during the lamination process of the second stacking sequence, no unequal pressure acts on the electro-optical functional film, that is, the pressure load is made uniform by the curable adhesive.
[0042] During the lamination process in step (d), the second stacking sequence is heated and pressure is applied, wherein the lamination is usually carried out within a specific (optional) temperature and pressure range, wherein a maximum temperature and a maximum pressure can always be specified depending on the process conditions selected in each case. As mentioned above, pressure is applied only when the optically transparent curable adhesive has such a strongly reduced viscosity (which is particularly preferably lower than the viscosity of the thermoplastic) that the local inhomogeneous pressure acting on the electro-optical functional film can be absorbed, in particular with a pressure effective for lamination, in particular with a maximum pressure of the second stacking sequence.
[0043] The optically transparent curable adhesive is preferably cured by applying pressure to the second stacking sequence, i.e. step (d) for laminating the second stacking sequence under the action of heat and pressure and step (e) for curing the optically transparent adhesive are preferably not carried out sequentially in time, but simultaneously. This has the advantage that, due to the highly fluid state of the adhesive layer, inhomogeneities can be compensated particularly well, and this state is then quasi-“maintained” by curing (always still under pressure).
[0044] Unlike the lamination methods known in the prior art, in the method according to the invention, uneven contact pressure on the electro-optical functional film is avoided and the risk of local defects in the electro-optical functional film is minimized. This is a major advantage of the invention.
[0045] In particular, the composite glass pane produced (obtained) by the method according to the present invention is generally used to separate an interior space from the external environment. The composite glass pane comprises a first glass pane having an outer side and an inner side and a second glass pane having an inner side and an outer side, which are firmly bonded to each other. The first glass pane can also be called an outer glass pane, and the second glass pane is called an inner glass pane. The surfaces or faces of the two single glass panes are respectively called face I, face II, face III and face IV from the outside to the inside. For example, the first glass pane is the outer glass pane of the composite glass pane, and the second glass pane is correspondingly its inner glass pane. In the installed state, the outer glass pane faces the external environment. The electro-optical functional film is located between the two single glass panes, i.e., integrated into the composite glass pane.
[0046] The film made of thermoplastic material softens due to the temperature increase during the lamination process, wherein in the composite glass plate, the first intermediate layer made of thermoplastic material is formed by the at least one first thermoplastic film, and the second intermediate layer made of thermoplastic material is formed by the at least one second thermoplastic film. This is correspondingly applicable to a frame made of thermoplastic material, which is fused with the thermoplastic intermediate layer during the lamination process. After lamination, the two thermoplastic layers and the frame made of thermoplastic are fused together. In this case, a layered frame can also be defined around the electro-optical functional film (at least in theory). The layered frame completely surrounds the electro-optical functional film without interruption in the manner of a picture frame edge, that is, completely surrounds the electro-optical functional film. The frame is a layered design, that is, a thermoplastic material layer, which surrounds the electro-optical functional film in a frame-like manner.
[0047] In the second stacking sequence, the at least one first thermoplastic plastic film, the first stacking sequence with the layered frame and the at least one second thermoplastic plastic film preferably have the same dimensions, ie are of equal size in terms of area.
[0048] The thermoplastic layer and the layered frame made of thermoplastic are provided in each case by at least one thermoplastic film. The first stacking sequence is preferably inserted into a cutout of at least one thermoplastic film for the layered frame. Preferably, the layered frame made of thermoplastic and the first stacking sequence have the same thickness so that the first stacking sequence does not protrude or recede relative to the layered frame (in a direction perpendicular to the electro-optical functional film).
[0049] The second stacking sequence is generated from the first stacking sequence, i.e. the first stacking sequence is a component of the second stacking sequence. The second stacking sequence is produced by embedding the first stacking sequence in a thermoplastic film, wherein at least one thermoplastic film is arranged on each side of the first stacking sequence. On both sides of the first stacking sequence, a first glass pane and a second glass pane are arranged on the thermoplastic film. The second stacking sequence is laminated by the action of heat and pressure, i.e. temperature increase and pressure application, wherein the optically transparent curable adhesive liquefies more strongly than the thermoplastic, so that at least from a certain (lowest) temperature, the viscosity of the optically transparent curable plastic is lower than the viscosity of the thermoplastic.
[0050] The optically transparent curable adhesive of the two adhesive films is curable, i.e. can be irreversibly brought into a cured state. Typically, it is a plastic that enters a polymer cross-linked state by curing. This makes the curable plastic significantly different from thermoplastics, which, although also optically transparent, can be softened reversibly by supplying heat. In contrast, the curable adhesive can no longer enter a fluid state once it has been cured. Therefore, the optically transparent curable adhesive is not a thermoplastic. In the sense of the present invention, the terms "curable adhesive" and "thermoplastic" should be understood in this sense.
[0051] The curable optically clear adhesive can be cured by the action of heat, electromagnetic radiation (preferably UV radiation) and / or chemically. The curing is preferably carried out by supplying heat or temperature increase and / or UV radiation.
[0052] Particularly preferably, the optically transparent curable adhesive is cured by supplying heat, wherein the curing of the curable adhesive can be carried out at the highest temperature used in the lamination process of the second stacking sequence in step (d) or at a temperature lower than this temperature. However, it is also possible that the curable adhesive is cured at a temperature higher than the highest temperature used in the lamination process of the second stacking sequence in step (d). In any case, the curable adhesive is first liquefied by heating (converted from a solid aggregate state to a liquid aggregate state) during the lamination process, and is cured (irreversibly converted from a liquid aggregate state to a solid aggregate state) during further heating. This represents a particularly effective method implementation in a very advantageous manner. Only when the curable adhesive has a sufficiently low viscosity (the viscosity is particularly preferably lower than the viscosity of the thermoplastic), pressure is applied to the second stacking sequence so that the local pressure difference can be absorbed during the lamination process. As previously mentioned, it is particularly preferred that there is at least one temperature range, wherein the viscosity of the optically transparent curable adhesive is lower than the viscosity of the thermoplastic. If the curable adhesive is cured at a temperature higher than the highest temperature used in the lamination process, the temperature of the second stacking sequence is further increased in a corresponding manner.
[0053] In the method according to the invention, the first stacking sequence is first formed and then arranged in the second stacking sequence. According to an advantageous embodiment of the method according to the invention, the first stacking sequence is designed as an adhesive precomposite, which can facilitate its embedding in the second stacking sequence. This can be achieved in a simple manner, for example, due to the adhesive properties of the two adhesive films. However, it is also possible that the first stacking sequence has no adhesive bond.
[0054] According to one embodiment of the method according to the invention, the second stacking sequence is evacuated before or during lamination, which has the advantage that air bubbles and other gaseous inclusions can be removed from the second stacking sequence.
[0055] The electro-optical functional film can be designed arbitrarily in principle. Electrically switchable or electrically controllable functional films are, for example, SPD (suspended particle device), PDLC (polymer dispersed liquid crystal), electrochromic or electroluminescent functional films, and are known per se to those skilled in the art. The functional film can also be a polymer conductive layer, which, for example, contains at least one conjugated polymer or a polymer equipped with conductive particles. Typically, the functional film contains at least one carrier film having a functional layer. The carrier film preferably contains a polymer, in particular polyvinyl butyral (PVB), ethylene vinyl acetate (EVA), polyurethane (PU), polyethylene terephthalate (PET) or a combination thereof.
[0056] In the case of a guest-host film with a functional layer made of a liquid crystal material containing embedded additives, the method according to the invention is particularly advantageous. Reference is made to the above statements about guest-host films. The person skilled in the art is well aware of the guest-host film itself, so it does not need to be discussed in more detail here. Guest-host films are commercially available, for example under the name of "light control film" (light control film), for example from Dai Nippon Printing Co., Ltd., Japan, under the product name LCF005 (EU). The electro-optical functional film is preferably a guest-host film.
[0057] In principle, the curable optically transparent (transparent) adhesive can be selected arbitrarily, provided that it is or can become viscous or liquid in the non-cured state (for example, by temperature increase) and is irreversibly curable. The transparent adhesive is, for example, based on silicone. Optically transparent adhesives are known by the abbreviation OCA (optically clear adhesive), wherein the abbreviation LOCA (liquid optically clear adhesive) is particularly used for liquid optically transparent adhesives. Optically transparent adhesives are characterized by high optical quality and are mainly used in places where a quasi-invisible adhesive layer is required, such as in the case of displays or touch panels. Optically transparent adhesives are therefore often used in touch-sensitive displays, for example to firmly bond them to LCD displays or even to firmly bond plastic covers to touch-sensitive displays. After application, the optically transparent adhesive is often cured by ultraviolet radiation. Optically transparent adhesives are freely commercially available from many suppliers.
[0058] The optically clear (transparent) curable adhesive may, for example, contain polyurethane (PU), polyacrylate, polyacetate resin, casting resin, silicone or copolymers or mixtures thereof, or consist of them. The optically clear adhesive advantageously contains a casting resin, in particular a casting resin based on polyurethane or silicone, or consists of them.
[0059] Depending on the adhesive used, the curing of the optically transparent adhesive can be achieved by thermal curing (i.e. supplying heat), by electromagnetic radiation, particularly ultraviolet radiation, infrared radiation or microwave radiation, by ultrasound, by water supply or by chemical reactions of various components (particularly two-component adhesives). In many curing processes, the time required for curing the optically transparent adhesive is affected by temperature. In particular, curing can be accelerated by supplying heat. On the contrary, curing can be slowed down by cooling. The curing time can be controlled, for example, by heating or cooling the optically transparent adhesive.
[0060] Each single glass pane of the composite glass pane (i.e. the first glass pane and the second glass pane) contains glass, particularly preferably flat glass, float glass, quartz glass, borosilicate glass, soda-lime glass, aluminosilicate glass, or transparent plastic, preferably hard transparent plastic, in particular polyethylene, polypropylene, polycarbonate, polymethyl methacrylate, polystyrene, polyamide, polyester, polyvinyl chloride and / or mixtures thereof, or preferably consists of them. Particularly preferably, each glass pane contains glass, in particular soda-lime glass, or consists of it. Suitable glasses are known, for example, from EP 0847965 B1.
[0061] The thickness of each individual glass pane of the composite glass pane can vary widely and be adjusted according to the requirements of the specific case. Preferably, glass panes with a standard thickness of 1.0 mm to 25 mm, preferably 1.4 mm to 2.1 mm, are used. The size of the glass panes can vary widely and depends on the application.
[0062] The composite glass pane can have any three-dimensional shape and can be flat or slightly or strongly curved in one or more directions in space. The composite glass pane preferably has a curvature, because the method according to the invention can be used particularly advantageously for curved composite glass panes. It should be understood that the two single glass panes of the composite glass pane are curved in a corresponding manner to match each other exactly. However, as usual, the two single glass panes are not fitted exactly (identical) before lamination, but rather have shape inaccuracies within the dimensional or production tolerances.
[0063] The thermoplastic layer and the layered frame made of thermoplastics contain polyvinyl butyral (PVB), ethylene vinyl acetate (EVA), thermoplastic polyurethane (TPU) and / or polyethylene terephthalate (PET), or preferably consist of them. The thermoplastic is formed by one or more thermoplastic films stacked on top of each other, wherein the thickness of the thermoplastic film is preferably 0.25 mm to 1 mm, typically 0.38 mm or 0.76 mm.
[0064] The layer and the layered frame can consist of the same thermoplastic or of thermoplastics that are different from one another. In the case of different thermoplastics, the statements about viscosity or flowability in the description of the invention relate to each thermoplastic.
[0065] In the sense of the present invention, "transparent" means that the total transmittance of the composite glass pane complies with the EU legal provisions for windshield panes and front side panes and preferably has a transmittance of more than 70%, in particular more than 75%, for visible light. For the rear side panes, roof panes and rear panes, "transparent" can also mean a transmittance of 10% to 70%. Thus, "opaque" means a transmittance of less than 15%, preferably less than 5%, in particular 0%.
[0066] The known methods for producing composite glass sheets can be used for lamination. For example, the so-called autoclave method can be carried out at a high pressure of about 1 bar to 15 bar and a temperature of 100° C. to 145° C. for about 2 hours. For example, the vacuum bag or vacuum ring method known per se operates at about 200 mbar and 130° C. to 145° C. The two glass sheets can also be pressed between at least one pair of rollers in a calender to form a composite glass sheet. This type of equipment for producing composite glass sheets is known and usually has at least one heating channel upstream of the pressing unit. The temperature during the pressing process is, for example, 40° C. to 150° C. The combination of the calendering method and the autoclave method has proven to be particularly successful in practice. Alternatively, a vacuum laminator can be used. These consist of one or more chambers that can be heated and evacuated, in which the first glass sheet and the second glass sheet can be laminated for example within about 60 minutes at a reduced pressure of 0.01 mbar to 800 mbar and a temperature of 80° C. to 170° C.
[0067] The invention further extends to a composite glass pane produced, in particular, by the method according to the invention, comprising in the following order a first glass pane, at least one first intermediate layer made of thermoplastic, a first adhesive layer made of an optically transparent cured adhesive, an electro-optical functional film, a second adhesive layer made of an optically transparent cured adhesive, at least one second intermediate layer made of thermoplastic, and a second glass pane, wherein the first adhesive layer, the electro-optical functional film and the second adhesive layer are surrounded by a layered frame made of thermoplastic.
[0068] The invention further extends to the use of the composite glass pane according to the invention in buildings or in land, air or water transportation vehicles, in particular in motor vehicles, for example as a windshield, rear glass, side glass and / or roof glass. Preference is given according to the invention to the use of the composite glass pane in motor vehicles, particularly preferably as a windshield or roof glass.
[0069] Various embodiments of the present invention can be realized alone or in any combination. In particular, the features described above and explained further below can be used not only in the combination shown, but also in other combinations or alone, without departing from the scope of the present invention.
[0070] The invention is explained in more detail below with reference to an embodiment, wherein reference is made to the accompanying drawings. In the simplified and not to scale illustrations:
[0071] Figure 1 shows a cross-sectional view of an intermediate product for producing a first stacking sequence having an electro-optical functional film,
[0072] Figure 2shows a cross-sectional view of a first stacking sequence having electro-optical functional films,
[0073] Figure 3 Shows a layered framework Figure 2 A top view of the first stacking sequence,
[0074] Figure 4 Shows a layered framework Figure 3 A cross-sectional view of the first stacking sequence,
[0075] Figure 5 Shows the Figure 3 and Figure 4 a cross-sectional view of a first stacking sequence and a second stacking sequence,
[0076] Figure 6 shows a cross-sectional view of an embodiment of a composite glass pane according to the invention,
[0077] Figure 7 A flow chart illustrating the method according to the invention is shown.
[0078] Reference Figures 1 to 6 , a method according to the invention for producing a composite glass pane and a composite glass pane according to the invention, which is denoted overall by the reference numeral 1 , are explained by way of example.
[0079] First consider Figure 1 and Figure 2 . Figure 1 A simplified schematic cross-sectional view of an intermediate product for forming a first stacking sequence 2 for use in the production of a composite glass panel 1 according to the invention is shown. In this case, a first adhesive film 4 made of an optically transparent curable adhesive is arranged on one side or surface of an electro-optical functional film 9. Figure 2 A first stacking sequence 2 is shown, wherein in addition to the first adhesive film 4, a second adhesive film 5 made of an optically transparent curable adhesive is arranged on the other or opposite side or surface of the electro-optical functional film 9. The curable adhesive of the first adhesive film 4 and the curable adhesive of the second adhesive film 5 can be the same or different from each other, preferably they are the same. The first stacking sequence 2 is generated as an adhesive pre-composite, which is easy to achieve because the two adhesive films 4, 5 here have, for example, adhesive (gluing) properties. This facilitates the further processing of the first stacking sequence 2.
[0080] The two adhesive films 4, 5 are provided with cover films on both sides, for example. To produce the first stacking sequence 2, for example, the cover film is first peeled off from the first adhesive film 4 and bonded to the electro-optical functional film 9 via its sticky side. Then the composite of the electro-optical functional film 9 and the first adhesive film 4 is turned over 180°, the cover film is peeled off from the second adhesive film 5, and the second adhesive film 5 is bonded to the electro-optical functional film 9 via its sticky side. At this point, the first stacking sequence 2 produced as an adhesive pre-composite has cover films on both surfaces, which makes it easy to store the first stacking sequence 1. For further processing of the first stacking sequence 2, the cover film is peeled off.
[0081] exist Figure 2 In the first stacking sequence 2 shown, the electro-optical functional film 5 is embedded between two adhesive films 4, 5, so that during the lamination process, the electro-optical functional film 5 is protected by the two adhesive films 4, 5. The electro-optical functional film 5 and the two adhesive films 4, 5 have the same size, that is, they are the same in terms of area.
[0082] Reference now Figure 3 and Figure 4 , which explains Figure 2 A first stacking sequence of layered frames 6 . Figure 3 A top view of a first stacking sequence 2 is shown, Figure 4 Shows the corresponding Figure 3 Cross-sectional view of cutting line AA in .
[0083] like Figure 3 It can be clearly seen that the first stacking sequence 2 is inserted into the cutout 7 of the thermoplastic frame film 8, which forms a layered frame 6 made of thermoplastic material for the first stacking sequence 2. The electro-optical functional film 9 is inserted into the cutout 7 so that the remaining part of the frame film 8 completely surrounds the electro-optical functional film 9. The cutout 7 is here introduced, for example, into the center of the frame film 8. The thickness of the frame 6 or frame film 8 made of thermoplastic material (i.e., the dimension perpendicular to the first stacking sequence 2) is the same as the thickness of the first stacking sequence 2, so that the first stacking sequence 2 does not protrude or retract relative to the frame 6 made of the thermoplastic material. Although Figure 4 Only a single frame film 8 is illustrated in FIG. 1 , but two or more frame films having a common cutout for the electro-optical functional film 9 may also be used.
[0084] Figure 5A second stacking sequence 11 is shown in a schematic cross-sectional view. It comprises, for example, in the center here, a first stacking sequence 2 with a frame 6 made of thermoplastic material. First glass panes 3 are arranged on one side of the first stacking sequence 2, with a first thermoplastic film 12 being placed between them. Second glass panes 10 are arranged on the other side of the first stacking sequence 2, with a second thermoplastic film 13 being placed between them.
[0085] The second stacking sequence 11 is laminated under increased temperature and applied pressure. First, the temperature of the second stacking sequence 11 is increased without applying pressure, which causes the two adhesive films 4, 5 made of optically transparent curable adhesive to melt and liquefy. In addition, the two thermoplastic films 12, 13 soften due to the increased temperature. After the two adhesive films 4, 5 have been liquefied, pressure is applied to the second stacking sequence 11 under further heating to laminate the two glass plates 3, 10, wherein the thermoplastic melts. Here, the liquefied optically transparent curable adhesive protects the electro-optical functional film 9 from uneven pressure during the lamination process. Pressure is applied to the second stacking sequence 11 only when the viscosity of the optically transparent curable adhesive of the two adhesive films 4, 5 is lower than the viscosity of the thermoplastic of the two thermoplastic films 12, 13. In other words, pressure is exerted on the second stacking sequence 11 only when the flowability of the optically transparent curable adhesive of the two adhesive films 4 , 5 is greater than the flowability of the thermoplastic of the two thermoplastic films 12 , 13 .
[0086] Even during the application of pressure during lamination, the two adhesive films 4, 5 are cured, for example by thermal curing, for which the second stacking sequence 11 is further heated to a temperature exceeding the maximum temperature used during lamination, although it is also possible that curing already occurs at the maximum temperature used during lamination. As is known to those skilled in the art, the second stacking sequence 11 can be evacuated during lamination. After the curable adhesive has cured, the composite glass pane 1 is firmly joined.
[0087] Figure 6 The composite glass pane 1 according to the invention is shown by way of example. Figure 5The second stacking sequence 11 is produced after lamination and adhesive curing. It comprises the first glass plate 3, the first intermediate layer 14 made of thermoplastic, the electro-optical functional film 9 surrounded by the layered frame 6 made of thermoplastic, the second intermediate layer 15 made of thermoplastic and the second glass plate 10 in the following order. Adjacent to the electro-optical functional film 9 are the first adhesive layer 16 made of cured adhesive and the second adhesive layer 17 made of cured adhesive. The first intermediate layer 14 made of thermoplastic, the thermoplastic frame 6 and the second intermediate layer 15 made of thermoplastic are fused together.
[0088] The composite glass panel 1 can be installed in a building or a motor vehicle to separate the interior space from the external environment. The composite glass panel 1 is, for example, a windshield panel of a motor vehicle. The first glass panel 3 and the second glass panel 10 are each composed of glass, preferably soda-lime glass, and are transparent to visible light. The thermoplastic plastic used in the composite glass panel 1 is preferably composed of polyvinyl butyral (PVB), ethylene vinyl acetate (EVA), thermoplastic polyurethane (TPU) and / or polyethylene terephthalate (PET).
[0089] The outer surface of the first glass plate 3 faces the external environment and is also the outer surface of the composite glass plate 1. The inner surface of the second glass plate 10 faces the interior space of the building or vehicle and is also the inner surface of the composite glass plate 1. It should be understood that the composite glass plate 1 can have any suitable geometric shape and / or curvature. As a windshield glass plate, the composite glass plate 1 usually has a convex curvature. Preferably, the electro-optical functional film 9 integrated into the composite glass plate 1 is a guest-host film as described above.
[0090] In the above-described method for producing the composite glass pane 1 , the first stacking sequence 2 is produced as an adhesive pre-composite. It is also conceivable that the first stacking sequence 2 is not produced as an adhesive pre-composite.
[0091] Figure 7 The method according to the invention is described again based on a flow chart. It comprises the following steps in the following order:
[0092] (a) forming a first stacking sequence 2, which comprises in the following order:
[0093] - a first adhesive film 4 made of an optically transparent curable adhesive,
[0094] -Electro-optical functional film 9,
[0095] - a second adhesive film 5 made of an optically transparent curable adhesive,
[0096] (b) forming a layered frame 6 made of thermoplastic material around the first stacking sequence 2,
[0097] (c) forming a second stacking sequence 11, which comprises in the following order:
[0098] - a first glass sheet 3,
[0099] - at least one first thermoplastic film 12,
[0100] a first stacking sequence 2 with a layered framework 6,
[0101] - at least one second thermoplastic film 13,
[0102] - a second glass plate 10,
[0103] (d) laminating the second stacking sequence 11 by the action of heat and pressure,
[0104] (e) curing the optically clear adhesive.
[0105] The optically transparent curable adhesive is designed such that a reduction in viscosity occurs by heating during the lamination process in step (d), wherein the viscosity of the curable adhesive particularly preferably decreases more strongly than the viscosity of the thermoplastic, wherein at least from a certain (minimum) temperature, the viscosity of the optically transparent curable adhesive is lower than the viscosity of the thermoplastic.
[0106] As can be seen from the above statements, the present invention provides an improved method for producing a composite glass pane with an integrated electro-optical functional film. Since the low-viscosity or liquefied adhesive compensates for the uneven mechanical load on both sides of the electro-optical functional film, it is avoided that an uneven pressure is applied to the electro-optical functional film between two glass sheets during the lamination process. The method according to the present invention can be implemented in a simple manner in the industrial mass production of composite glass panes. Composite glass panes with an integrated electro-optical functional film can be produced simply and cost-effectively and have high optical quality.
[0107] List of reference numerals:
[0108] 1 Composite glass panel
[0109] 2 First stacking sequence
[0110] 3 First Glass Plate
[0111] 4. First adhesive film
[0112] 5 Second adhesive film
[0113] 6 Framework
[0114] 7. Incision
[0115] 8 Frame film
[0116] 9 Electro-optical functional film
[0117] 10 Second Glass Plate
[0118] 11 Second stacking sequence
[0119] 12. The first thermoplastic film
[0120] 13. Second thermoplastic film
[0121] 14 First Intermediate Layer
[0122] 15 Second intermediate layer
[0123] 16 First adhesive layer
[0124] 17 Second adhesive layer
Claims
1. A method for producing a composite glass panel (1), comprising the following steps: (a) forming a first stacking sequence (2), They include, in the following order: - a first adhesive film (4) made of an optically transparent curable adhesive, - electro-optical functional film (9), - a second adhesive film (5) made of an optically transparent curable adhesive, (b) forming a layered frame (6) made of thermoplastic material around the first stacking sequence (2), (c) forming a second stacking sequence (11) comprising, in the following order: - a first glass sheet (3), - at least one first thermoplastic film (12), - a first stacking sequence (2) having a layered framework (6), - at least one second thermoplastic film (13), - a second glass sheet (10), (d) laminating said second stacking sequence (11) by the action of heat and pressure, (e) curing the optically clear adhesive.
2. The method according to claim 1, wherein the curable adhesive is designed so that a viscosity reduction occurs by heating during the lamination process in step (d), wherein the viscosity of the curable adhesive decreases more strongly than the viscosity of the thermoplastic.
3. A method according to claim 1 or 2, wherein pressure is applied to the second stacking sequence (11) in step (d), in particular a pressure effective for lamination, only when the viscosity of the curable adhesive reduced by heating during the lamination process in step (d) is lower than the viscosity of the thermoplastic reduced by heating during the lamination process in step (d).
4. A method according to any one of claims 1 to 3, wherein the curable adhesive is cured by the action of heat.
5. The method according to claim 4, wherein the curable adhesive cures at or below the highest temperature used during lamination of the second stacking sequence (11) in step (d).
6. The method according to claim 4, wherein the curable adhesive is cured at a temperature higher than the highest temperature used during lamination of the second stacking sequence (11) in step (d).
7. The method according to any one of claims 1 to 3, wherein in step (e) the curable adhesive is cured by the action of electromagnetic radiation and / or chemically.
8. The method according to any one of claims 1 to 7, wherein the optically clear adhesive is cured during the application of pressure in step (d) during the lamination of the second stacking sequence (11).
9. The method according to any one of claims 1 to 8, wherein the first stacking sequence (2) is formed as an adhesive pre-composite.
10. The method according to any one of claims 1 to 9, wherein the first stacking sequence (2) is inserted into a cutout (7) of at least one thermoplastic film (8) in order to form the layered frame (6).
11. The method according to any one of claims 1 to 10, wherein in step (d) the second stacking sequence (11) is evacuated during the lamination process.
12. The method according to any one of claims 1 to 11, wherein the electro-optical functional film (9) comprises a guest-host film having a functional layer made of a liquid crystal material comprising an embedded additive.
13. The method according to any one of claims 1 to 12, wherein the first glass pane (3) and / or the second glass pane (10) consists of glass, in particular soda-lime glass.
14. Composite glass pane (1), in particular obtained by a method according to any one of claims 1 to 13, comprising in the following order: - a first glass sheet (3), - at least one first intermediate layer (14) made of thermoplastic, - a first adhesive layer (16) made of an optically transparent cured adhesive, an electro-optical functional film (9), a second adhesive layer (17) made of an optically transparent cured adhesive, wherein the first adhesive layer (16), the electro-optical functional film (9) and the second adhesive layer (17) are surrounded by a layered frame (6) made of thermoplastic, - at least one second intermediate layer (15) made of thermoplastic, - A second glass sheet (10).
15. Use of a composite glass pane (1) according to claim 14 in buildings or in land, air or water vehicles, in particular in motor vehicles, for example as a windshield, rear window, side window and / or roof window.
Citation Information
Patent Citations
Glazing comprising a substrate furnished with a multiplicity of thin layers providing thermal insulation and / or solar protection
EP0847965B1
Method for producing a composite pane with a functional element
WO2021069354A1
Method for laminating a laminated pane comprising a functional element with electrically switchable optical properties
WO2021249801A1